Evaluation of Electronic Medical Record Quality from the Perspective of Data Security - Riska Rosita; Yunita Wisda Tumarta Arif; Naufal Rohman Wachid (GLOBAL HEALTH SCIENCE GROUP, 2026)
All health care facilities in Indonesia are required to implement Electronic Medical Records (EMR), including Community Health Centers. The implementation of EMR has various challenges such as the threat of electronic data theft, data loss, and data leakage Objective: to evaluate the quality of EMR data security at Community Health Center X based on the Peraturan Menteri Kesehatan nomor 24 tahun 2022. This is a descriptive qualitative study with a cross-sectional approach. The subjects of the study were 8 respondents, namely, including registration unit officers, general practitioner, midwife at a maternal and child health (KIA) clinic, laboratory head, administrative head, pharmacy staff member, and medical records head. The object of the study is the EMR system. Data collection through observation checklists and in-depth interviews. Observation data were analyzed descriptively, while interview data were analyzed with thematic/framework analysis. The study shows that based on the confidentiality aspect, all officers still use the same account when logging into EMR. Community Health Center X does not yet have a feature to document the audit trail process. In terms of integrity, the use of digital signatures is replaced with clear names filled in using passwords. In terms of availability, Community Health Center X stores patient data on the server and has backed up data periodically, EMR has an ID feature to download patient data. Data security is important in the implementation of the Electronic Medical Records (EMR) system to ensure the quality and confidentiality of medical information.